2017
DOI: 10.1093/cid/cix606
|View full text |Cite
|
Sign up to set email alerts
|

Empiric Therapy With Carbapenem-Sparing Regimens for Bloodstream Infections due to Extended-Spectrum β-Lactamase–Producing Enterobacteriaceae: Results From the INCREMENT Cohort

Abstract: We were unable to show that empiric treatment with OAD was associated with a worse outcome compared with carbapenems. This information allows more options to be considered for empiric therapy, at least for some patients, depending on local susceptibility patterns of ESBL-E.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 26 publications
0
35
0
2
Order By: Relevance
“…Using INCREMENT cohort data, Palacios-Baena et al compared the empirical use of drugs other than carbapenems or BLBLIs (86 patients; 43 received an aminoglycoside) and carbapenems (249 patients) for BSI due to ESBL producers for mortality, clinical cure, and length of hospital stay. No significant differences (or trends) in any outcome were shown (106). Toxicity was not formally evaluated, but significant toxicity would be expected to have some effect on length of stay.…”
Section: Aminoglycosidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using INCREMENT cohort data, Palacios-Baena et al compared the empirical use of drugs other than carbapenems or BLBLIs (86 patients; 43 received an aminoglycoside) and carbapenems (249 patients) for BSI due to ESBL producers for mortality, clinical cure, and length of hospital stay. No significant differences (or trends) in any outcome were shown (106). Toxicity was not formally evaluated, but significant toxicity would be expected to have some effect on length of stay.…”
Section: Aminoglycosidesmentioning
confidence: 99%
“…According to these data, the current EUCAST susceptibility breakpoint (Յ0.25 mg/liter) seems to be more appropriate than the breakpoint of Յ1 mg/liter recommended by CLSI, at least for ESBL-E. The study by Palacios-Baena et al mentioned above, which examined the outcomes for patients with BSI due to ESBL-E who were treated empirically with active drugs other than BLBLIs or carbapenems, included 19 patients treated with a fluoroquinolone as the only active drug according to CLSI breakpoints, and the mortality rate was 10.5%, similar to that for patients treated with carbapenems (106).…”
Section: Fluoroquinolones and Trimethoprim-sulfamethoxazolementioning
confidence: 99%
“…These findings have important implications for the management of the increasingly common problem of ESBL-producing E. coli bacteremia in these vulnerable patients (14). Previous studies conducted in general patient populations have identified an increased risk of treatment failure with cefepime as empiric therapy for ESBL-producing E. coli bacteremia, while retrospective studies evaluating piperacillin-tazobactam as empiric therapy for these infections have shown conflicting results (6,9,11,15,16). A recent international, multicenter study conducted by Gudiol et al comparing BLBLI combination therapy to carbapenems for the treatment of ESBL-producing Enterobacteriaceae bacteremia in neutropenic patients with hematologic malignancy identified a…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, evidence is emerging that empiric or definitive treatment with BL/BLIs is probably as effective as carbapenem therapy in the setting of ESBL (E. coli or K. pneumoniae) bacteremia (9-11). Data regarding the usefulness of carbapenem-sparing antibiotics other than BL/BLIs for definitive treatment have also been reported, though also within an IV regimen (12-14). The effectiveness of non-intravenous (oral or intramuscular) antibiotic treatment for the management of ESBL or Amp-C bacteremia has not been widely assessed to date (3, 15).…”
Section: Introductionmentioning
confidence: 99%